Plural Identity and Migrant Communities in Guy Gunaratne’s In Our Mad and Furious City (2018) - Margarida Pereira Martins (Anglica. An International Journal of English Studies)
This paper explores the complexity of plural identities of the characters living within the sociocultural space of a London community, who define themselves as being from “here” and “elsewhere,” in Guy Gunaratne’s In Our Mad and Furious City (2018). First-generation and second-generation migrants, originally from Ireland, Pakistan, Jamaica, as well as other nations referred to in the novel, give life to the community at the Ends, a housing estate in Northwest London. On the one hand, in this suburban space, fury, neglect and powerlessness are deeply felt by the locals. However, the community also becomes the location for the creation of social habits, cultural patterns, forms of ex- pression and group unity through the interaction and shared experiences of the locals. This dichotomy reveals underlying anxieties that raise questions about otherness, marginalisation and belonging, and how these aspects intersect in the construction of cultural identity. As characters struggle for meaning against a “cancel culture,” their individual experiences are what constitutes their plural and fluid identities.